New concepts in the early and preclinical detection of Parkinson's disease: therapeutic implications. (December 2012) - Akhtar, Rizwan S; Stern, Matthew B
Parkinson's disease is a chronic neurodegenerative disorder leading to progressive motor impairment for which there is no cure. Currently, the diagnosis is made by the presence of cardinal motor features and several associated non-motor symptoms. However, at this point, the underlying neuropathological changes are already underway, and efforts in basic and clinical research have converged to suggest that Parkinson's disease actually begins well before symptom onset. As a result, the identification and development of disease-modifying therapies is difficult. In this review, we begin by summarizing what is known of disease pathogenesis in the context of early symptomatology. We then discuss the Parkinson's at-risk syndrome and highlight how this conceptual framework can be a useful for studies of early disease biomarkers and putative disease-modifying neurotherapeutics. With this framework, we discuss several clinical assessments, radiological studies and molecular assays that may be useful in early disease detection.